Synthesis of nickil (ii) complex of taazatricyclotetracosane (octc) macrocyclic complexes from the contaminated soil - SANGEETA SAHU,; SMITA SAHU, (International Journal of Pharma and Bio Sciences, 2016)
Consumer demand for better quality produce is now on an increasing surge. In particular, some metals are not desirable in agriculture as they may harm the environment or humans. Because of this, the concentrations of metals in soils and foods should be regularly monitored. This paper extensively addresses our concerns about these undesired metals in the farm soil and farm produce and how to manage the situation so that it does not become a menace. This paper deals with the synthesis and characterization of macro cyclic ligand and its complex compound. Template condensation of chlorocarbons such as 1,1,2,2-tetrachloroethane with 1,3-diaminopropane in presence of nickel (II)) yielded the corresponding metal complexes such as 3,7,10,14,15,19,20,24- octaazatricyclotetracosane (OCTC). The macrocyclic ligands and their complexes have been characterized by elemental analysis, molecular weight determination, conductance, IR and NMR spectral studies. The magnetic moments, along with electronic spectral data suggested hexa coordinated state for Nickel, its geometry is outer orbit octahedral .Conductivity data suggests that they behave as electrolytes. The formulation of the complexes has been established on the basis of chemical composition. The significant ligand and their complexes have now widely being used as a catalyst in many industries.